Synthesis and Aggregation-Induced Emission Properties of New Carbazole-Based Pyranones and their Ring-Transformed Derivatives - Vats, Ravi Prakash; Pandey, Priyanka; Gupta, Shashwat; Gupta, Suchitra; Pal, Shyamal; Goel, Atul (Synthesis, 2024)
A new series of N-phenyl-carbazole (N-phCbz) appended pyranones were designed and synthesized using α-oxo-ketene-S,S-acetal under mild reaction conditions in good yields. The reactivity of donor-acceptor (D-A)-based 2H-pyranones was utilized to develop their ring-transformed benzene-cored N-phenyl-carbazole derivatives. All the synthesized carbazole-based pyranones showed aggregation-induced emission (AIE) characteristics in 80–99% water fraction (fw) in DMSO. Among all the synthesized compounds, 6-(4-(9H-carbazol-9-yl)phenyl)-4-(methylthio)-2-oxo-2H-pyran-3-carbonitrile exhibited excellent AIE behavior with ca. 70-fold increase in fluorescence in 80% fw at 550nm. Furthermore, this compound showed exceptionally high fluorescence in nonpolar solvent (THF) as compared to polar solvents such as DMSO (ca. 200-fold increase in fluorescence). The DFT, DSC, and TGA analyses of the synthesized D-π-A compounds suggested the strong electron-donor ability of N-phCbz, with good thermal stability in the range of 231–393 °C. These N-phenyl-carbazole-appended pyranones with interesting AIE properties have great potential as probes for bioimaging applications as well as for optoelectronic materials.
Keywords: carbazole; donor-acceptor; 2H-pyranones; AIE; fluorescent probes; bioimaging